(untitled) (Academicia Globe: Inderscience Research, 2021)
This article examines the persistent corpus luteum, the causes of infertility among cows, quantitative levels of steroid hormones in the serum of experimental cows, experimental cows were fertilized twice at 12-hour intervals using the manoservical method, and 3 months after insemination, cows were examined by commission-rectal studies. The application of symptomatic and operative therapies in the treatment of persistent corpus luteum, and the results of experiments, discussions were noted.